'Islam' and the Decline of Civilization: Deconstruction of Historiosophy of Oswald Spengler and Henri Pierenne - Boayo, Suleiman M. H. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
'Islam' and the Decline of Civilization: Deconstruction of Historiosophy of Oswald Spengler and Henri Pierenne